2018
DOI: 10.3390/nu10091135
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Melatonin Supplementation Could Be a Promising Preventing/Therapeutic Approach for a Variety of Liver Diseases

Abstract: In the therapeutic strategies, the role of diet is a well-established factor that can also have an important role in liver diseases. Melatonin, identified in animals, has many antioxidant properties and it was after discovered also in plants, named phytomelatonin. These substances have a positive effect during aging and in pathological conditions too. In particular, it is important to underline that the amount of melatonin produced by pineal gland in human decreases during lifetime and its reduction in blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 230 publications
(289 reference statements)
1
38
0
Order By: Relevance
“…Indeed, cisplatin predominantly exerted a cytostatic action that led to a reduction in cell proliferation over time, whereas 5-FU triggered reactive oxygen species-dependent apoptosis, resulting in a drastic decrease in cell viability ( Pariente et al, 2017 , 2018 ). Likewise, melatonin has been proven to attenuate antitumor actions of cisplatin in human liver carcinoma HepG2 cells via a counter-balance between the roles of apoptotic- and autophagy-related proteins ( Bennukul et al, 2014 ; Bonomini et al, 2018 ). Despite this, it has been observed that melatonin enhances cisplatin-induced cytotoxicity in different human ovarian cancer cells, like SKOV3, HTOA, and OVCAR-3 ( Futagami et al, 2001 ; Kim et al, 2012 ; Pariente et al, 2017 ).…”
Section: Melatoninmentioning
confidence: 99%
“…Indeed, cisplatin predominantly exerted a cytostatic action that led to a reduction in cell proliferation over time, whereas 5-FU triggered reactive oxygen species-dependent apoptosis, resulting in a drastic decrease in cell viability ( Pariente et al, 2017 , 2018 ). Likewise, melatonin has been proven to attenuate antitumor actions of cisplatin in human liver carcinoma HepG2 cells via a counter-balance between the roles of apoptotic- and autophagy-related proteins ( Bennukul et al, 2014 ; Bonomini et al, 2018 ). Despite this, it has been observed that melatonin enhances cisplatin-induced cytotoxicity in different human ovarian cancer cells, like SKOV3, HTOA, and OVCAR-3 ( Futagami et al, 2001 ; Kim et al, 2012 ; Pariente et al, 2017 ).…”
Section: Melatoninmentioning
confidence: 99%
“…Besides the significant influence of the light-dark cycle, nutritional factors such as macro-and micro-nutrient intake, meal timing, and type of diet can also modulate the concentration of melatonin in plasma [8]. The inclusion of melatonin-rich plant foods in the diet may promote human health owing to its biological activities and bioavailability [9,10]. Melatonin is broadly used as a food supplement worldwide, including in the United States and Europe, to counteract physiologically diminished activity of the pineal gland [11].…”
Section: Introductionmentioning
confidence: 99%
“…MLT, an indoleamine physiologically produced by the pineal gland mainly during the night as well by other organs, is often available as a dietary supplement [11][12][13]. It is involved in several functions and has powerful antioxidant properties [14][15][16][17]. MLT also improves endothelial functions and possesses anti-inflammatory properties [18].…”
Section: Introductionmentioning
confidence: 99%